Writing (from) the rubble - El Hajj, Sleiman (2020)
This reflexive piece integrates its author’s experience of Beirut’s August 4, 2020 port explosion with those of other Lebanese citizens writing on the heels of the calamity. The overall narrative approximates a collective biography that apprises and appraises the emergent fears, concerns, and anxieties roiling the country at present. I explore a lived, critically informed, spectrum of post-traumatic behaviours and responses to the widespread destruction and its implications – whether that be the loss of limb, home, or the physical loci of emotional memories, including cultural and heritage sites. The narrative also makes a connection between the recent explosion and earlier iterations of warfare and/or terrorism to show how the long-standing inability to functionally articulate and process pain is now translating into retributive calls for violent justice in a country still recovering from civil war.